Cross-cultural adaptation of the Activities of Daily Living Questionnaire-Brazil in Parkinson’s disease - ALVES, Walter Luis Teixeira; FARIA-FORTINI, Iza de; GALVÃO, Ana Carolina Daher Ribas; CARDOSO, Francisco Eduardo Costa; SCALZO, Paula Luciana (Arquivos de Neuro-Psiquiatria, 2021)
Background: Culturally adapted measures to assess the performance of activities of daily living (ADL) in individuals with Parkinson’s disease (PD) are limited in Brazil. Objective: To adapt the ADL Questionnaire to the Brazilian culture and to analyze its reproducibility in individuals with PD. Methods: The ADL Questionnaire was translated and cross-culturally adapted to Brazilian Portuguese language. Reproducibility was analyzed using test-retest reliability and agreement values. The test-retest reliability of the individual items and total scores were calculated. The limits of agreement were verified using the Bland-Altman plot. The standard error of measurement (SEM) and the minimum detectable change (MDC) were calculated. Patients who were classified on a score of 1–4 on the modified Hoehn and Yahr scale were eligible. Results: No divergence was identified between the original and the adapted version, which demonstrated adequate semantic and conceptual equivalence. The Bland-Altman plot showed no systematic changes in the mean test-retest scores. The intraclass correlation coefficient (ICC) was 0.98 (95% confidence interval [95%CI] 0.93–0.99), and all individual items showed good levels of reliability (>0.60). The SEM (SEM%) and MDC (MDC%) values were 3.0 (6.75%) and 8.2 (18.7%), respectively. These values are within the recommended values. Conclusions: The ADL-Brazil Questionnaire is a reliable instrument to be used for clinical and research purposes to assess self-perceptions of ADL performance in individuals with PD.
Keywords: Parkinson Disease; Activities of Daily Living; Reproducibility of Results